Overexpression of Specific CD44 Isoforms Is Associated with Aggressive Cell Features in Acquired Endocrine Resistance - Bellerby, Rebecca; Smith, Chris; Kyme, Sue; Gee, Julia; Günthert, Ursula; Green, Andy; Rakha, Emad; Barrett-Lee, Peter; Hiscox, Stephen (Frontiers in Oncology, 2016)
While endocrine therapy is the mainstay of ER+ breast cancer, the clinical effectiveness of these agents is limited by the phenomenon of acquired resistance that is associated with disease relapse and poor prognosis. Our previous studies revealed that acquired resistance is accompanied by a gain in cellular invasion and migration and also that CD44 family proteins are overexpressed in the resistant phenotype. Given the association of CD44 with tumor progression, we hypothesized that its overexpression may act to promote the aggressive behavior of endocrine-resistant breast cancers. Here, we have investigated further the role of two specific CD44 isoforms, CD44v3 and CD44v6, in the endocrine-resistant phenotype. Our data revealed that overexpression of CD44v6, but not CD44v3, in endocrine-sensitive MCF-7 cells resulted in a gain in EGFR signaling, enhanced their endogenous invasive capacity, and attenuated their response to endocrine treatment. Suppression of CD44v6 in endocrine-resistant cell models was associated with a reduction in their invasive capacity. Our data suggest that upregulation of CD44v6 in acquired resistant breast cancer may contribute to a gain in the aggressive phenotype of these cells and loss of endocrine response through transactivation of the EGFR pathway. Future therapeutic targeting of CD44v6 may prove to be an effective strategy alongside EGFR-targeted agents in delaying/preventing acquired resistance in breast cancer.